The impact of street characteristics on older pedestrians’ perceived safety in Shanghai, China - Hao Wu; Zhaoxi Zhang; Yong Chen; Junfeng Jiao (Journal of Transport and Land Use)
Land-use patterns and rapid urban sprawl greatly influence older adults’ mobility in China. Older pedestrians’ safety issues are crucial because these people are more frequently injured in traffic accidents. This research aims to investigate what street characteristics influence perceived safety among older pedestrians in Shanghai, China. A mix of research methods containing both quantitative and qualitative analyses were employed. The researchers recruited 68 elderly urban dwellers who each agreed to take a perceived safety survey using 39 simulated streetscape images that contained 12 street characteristics extracted from four sectional zones of streets. Ordinal logit regression was performed to investigate the impact of street characteristics on older pedestrians’ perceived safety. A semi-structured, in-depth interview was conducted with 8 out of the 68 participants. It was found that the street interface type, elevation differences, footpath width, paver directions, isolation facility type, and vehicle traffic all affected pedestrians’ perceived safety after adjusting for individual demographic attributes and the physical limitations of the participants. Understanding the street characteristics related to perceived safety will contribute to making more inclusive and walkable cities.